Interpretation of legal norms - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Scientific review of the monograph of V. G. Rotan, I. L. Samsin, A. G. Yarema et al. "Newest teaching of interpretation of legal norms: tutorial on course of interpretation of legal norms for judges who are advanced training, and candidates for judges who are trained".